Finite size effects in the study of equation of state for the nuclei with skyrme force : a thesis presented in partial fulfilment of requirements for the degree of Master in Physics at Massey University, Palmerston North, New Zealand - Al Harthi, Khlood Fahad (Massey University, 2017)
The equation of state for symmetric nuclear matter and nite nuclei has been investigated using self-consistent Hartree Fock approach. Several versions of Skyrme e ective interaction and Hill-Wheeler formula are employed in the calculation. The nite size e ect parameter aF , which is introduced into the Hill-Wheeler formula, is determined by comparing theoretical calculations and experimental results for the zero temperature properties. The dependence of aF on the e ective interaction employed has been studied. It was found that di erent versions of Skyrme force lead to di erent values for aF apart from SKI and SKIII which gave a similar value. Also, the aF values obtained with Skyrme interaction were di erent from what was obtained with Gogny force with the exception of SKV interaction which gave a value of aF = 0:35 identical to the value obtained with D1 Gogny interaction. The critical points of the rst order phase transition for the nuclear matter and nite size nuclei calculated with the several versions of Skyrme force were di erent from each other. The largest value of critical temperature for nuclear matter is given by SKV force as Tc = 39:45 MeV, while SKIII interaction gives the smallest value as Tc = 21:65 MeV. Similarly, the largest value of the critical density is given by SKV interaction. The critical points depend on the number of nucleons in the system and Tc decreases as the number of nucleons in the system decreases.
Keywords: Nuclear matter; Equations of state; Research Subject Categories::NATURAL SCIENCES::Physics::Nuclear physics